Characterization of prodigiosin pigment by Serratia marcescens and the evaluation of its bioactivities - Koyun, Merve Tunca; Sirin, Seda; Aslim, Belma; Taner, Gokce; Dolanbay, Serap Nigdelioglu (Pergamon-Elsevier Science Ltd, 2022)
The aim of the present study is to discover a bacterial pigment providing protection and prevention of neurological damage and cancer development, which can have a role as a non-synthetic food additive in the food industry as well as an active drug ingredient of anticancer drugs and pharmaceuticals for neural injury. Within this scope, Serratia marcescens MB703 strain was used to produce prodigiosin. Characterization of the prodigiosin was carried out using UV-VIS, and FT-IR. In addition, its inhibitory action on AChE and antioxidant activities were determined. The cytotoxic, genotoxic and antigenotoxic activities of the prodigiosin as well as its anti proliferative activities were detected. It was determined that the maximum production of the prodigiosin (72 mg/L). The prodigiosin was found to cause no significant difference in its inhibitory effect on AChE. The prodigiosin was found effective on all antioxidant parameters tested. The IC50 values of the prodigiosin on SK-MEL30 and HT-29 cells were calculated as 70 and 47 mu M, respectively. This IC50 values of the prodigiosin showed no cytotoxic effect on L929 cells. Prodigiosin did not have genotoxic effect alone and also seem to decrease DNA damage induced by H2O2 in L929 cells. The findings of in vitro experimental studies suggest that using the prodigiosin pigment as a drug candidate for cancer and neurodegenerative disease therapy is both effective and safe.
Keywords: Anticancer activity; FT-IR; HT-29 human colon cancer cells; Neuroprotective effect; Prodigiosin pigment; Serratia marcescens; SH-SY5Y human neuroblastoma cells; SK-MEL-30 human melanoma cancer; UV-VIS spectroscopy